The link between NBTI and TDDB of high-k gate P-MOSFETs - Gao, Yuan (2013)
The relationship between NBTI and TDDB of Hf-based high-k p-MOSFETs is examined. At certain NBTI stressing conditions, the conversion of switching hole traps into permanent trapped holes will occur to reduce the NBTI recovery. The conversion is shown to correspond to a degradation of the TDDB lifetime. This evidence implies switching hole traps as a common link between NBTI and TDDB.